2013
DOI: 10.1366/12-06952
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Pressure-Dependent Emission Characteristics in Different Gas Plasmas Induced by Nanosecond and Picosecond Neodymium-Doped Yttrium Aluminum Garnet (Nd:YAG) Lasers

Abstract: An experimental study has been performed on the pressure-dependent plasma emission intensities in Ar, He, and N2 surrounding gases with the plasma induced by either nanosecond (ns) or picosecond (ps) yttrium aluminum garnet laser. The study focused on emission lines of light elements such as H, C, O, and a moderately heavy element of Ca from an agate target. The result shows widely different pressure effects among the different emission lines, which further vary with the surrounding gases used and also with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Ar ambient gas is chosen in this study as it was shown to give the maximum emission intensity of the ablated atoms in a previous study. 21) It is found that almost the same plasma size of 20 mm diameter is obtained for both ps and ns laser irradiations using 150 Pa Ar ambient gas.…”
Section: Methodsmentioning
confidence: 67%
See 2 more Smart Citations
“…Ar ambient gas is chosen in this study as it was shown to give the maximum emission intensity of the ablated atoms in a previous study. 21) It is found that almost the same plasma size of 20 mm diameter is obtained for both ps and ns laser irradiations using 150 Pa Ar ambient gas.…”
Section: Methodsmentioning
confidence: 67%
“…The experimental setup used in this study is basically the same as the one described in our previous report. 21) The chamber used is the same special cylindrical chamber of 115 mm inner diameter, which was designed with several entry ports to allow for the control and monitoring of the specific conditions inside the chamber as needed for the experiment. For the current experiment, a ps Nd:YAG laser (Ekspla PL 2143, 1,064 nm, 20 ps, maximum energy of 30 mJ) and a ns Nd:YAG laser (Quanta Ray Lab Series 1,064 nm, 8 ns, maximum energy of 450 mJ) are employed separately, and are operated in the same Q-switched mode at 10 Hz repetition rate and the same fixed laser output energy of 25 mJ for a reason explained later.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation